Reduced long-term care cost by social participation among older Japanese adults: a prospective follow-up study in JAGES - Saito, Masashige (BMJ Open, 2019)
OBJECTIVES: Reducing costs related to functional disabilities and long-term care (LTC) is necessary in ageing societies. We evaluated the differences in the cumulative cost of public LTC insurance (LTCI) services by social participation. DESIGN: Prospective observational study. SETTING: Our baseline survey was conducted in March 2006 among people aged 65 or older who were not eligible for public LTCI benefits and were selected using a complete enumeration in Tokoname City, Japan. We followed up with their LTC services costs over a period of 11 years. Social participation was assessed by the frequency of participation in clubs for hobbies, sports or volunteering. We adopted a classical linear regression analysis and an inverse probability weighting (IPW), with multiple imputation of missing values. PARTICIPANTS: Functionally independent 5377 older adults. PRIMARY OUTCOME MEASURES: The cumulative cost of public LTCI services for 11 years. RESULTS: Even when adjusting for the confounding variables, social participation at the baseline was negatively associated with the cumulative cost of LTCI services. The IPW model showed that in respondents who participated in hobby activities once a week or more, the cumulative cost of LTCI services for 11 years was lower, approximately US$3500 per person, in comparison to non-participants. Similarly, that in respondents who participated in sports group or clubs was lower, approximately US$6000 than non-participants. CONCLUSIONS: Older adults’ participation in community organisations may help reduce future LTC costs. Promoting participation opportunities in the community could ensure the financial stability of LTCI services.